Northeast Minneapolis railroad tracks (Minnesota Streetcar Museum; http://www.trolleyride.org)
213ad240f3f38f057552be4970558ec0
United States
Minnesota
Hennepin
Northeast
Minneapolis
Keywords: streetcars; Twin City Rapid Transit Co.; street scene; Transportation